Analisis Yuridis Pembatalan Putusan Penundaan Kewajiban Pembayaran Utang dan Kepailitan melalui Upaya Hukum Peninjauan Kembali (Studi Kasus Putusan Mahkamah Agung Nomor: 24 PK/Pdt.Sus-Pailit/2024) - Elvinus Engel, Justi; Markoni; I Made Kantika; Joko Widarto; Tuti Elawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze legal certainty and the legal consequences of the annulment of Suspension of Debt Payment Obligations (PKPU) and bankruptcy decisions through Judicial Review in Supreme Court Decision Number 24 PK/Pdt.Sus-Pailit/2024. The research method employs normative legal research with statutory, conceptual, and case approaches, analyzed through the theory of legal certainty and the theory of legal protection. The results show that the annulment of PKPU and bankruptcy decisions through Judicial Review creates legal uncertainty because it eliminates all legal consequences of the Commercial Court and cassation decisions that had obtained permanent legal force. The annulment restores the debtor’s legal status, but at the same time reduces legal certainty for creditors, raises issues regarding the validity of the curator’s actions, and potentially triggers further disputes in bankruptcy proceedings. The study concludes that the availability of cassation and Judicial Review in PKPU cases following Constitutional Court Decision Number 23/PUU-XIX/2021 prolongs debt settlement and weakens the character of PKPU as a fast and final mechanism. Therefore, stricter normative limitations on the use of extraordinary legal remedies are required to maintain a balance between legal certainty and legal protection for both debtors and creditors. Keywords: Annulment of Judgment, Bankruptcy, Judicial Review, Legal Certainty, Suspension of Debt Payment Obligations.